2017
DOI: 10.1590/1809-4392201700993
|View full text |Cite
|
Sign up to set email alerts
|

Bat necrophagy by a whip-spider (Arachnida, Amblypygi, Phrynidae) in a cave in the eastern Brazilian Amazon

Abstract: Amblypygids are among the main predators in the ferriferous caves in Carajás National Forest, state of Pará (Amazon region of Brazil). One of the most common amblypygid species in this region is Heterophrynus longicornis (Butler 1873), and its most frequent prey are crickets of the family Phalangopsidae, which are abundant in the caves of Pará. Because they are primarily predators, necrophagy by amblypygids is not frequent in nature, and there are only two literature records of necrophagy of bats by Amblypygi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Armas & Abreu-Collado (1999) mentioned for the same species a similar case observed in a Hispaniolan cave [it was mentioned with some doubt by Armas & Pérez-Gonzalez (2001) and Armas (2006)]. A few years later, García-Rivera et al (2009) recorded three specimens of the Cuban large amblypygid Paraphrynus robustus Franganillo, eating on two dead bats, and recently, Prous et al (2017) reported bat necrophagy by the large South American amblypygid Heterophrynus longicornis Butler. Now, it is out of any doubt that necrophagy might be a frequent behavior in natural populations of some whip spiders.…”
Section: Preysmentioning
confidence: 73%
See 2 more Smart Citations
“…Armas & Abreu-Collado (1999) mentioned for the same species a similar case observed in a Hispaniolan cave [it was mentioned with some doubt by Armas & Pérez-Gonzalez (2001) and Armas (2006)]. A few years later, García-Rivera et al (2009) recorded three specimens of the Cuban large amblypygid Paraphrynus robustus Franganillo, eating on two dead bats, and recently, Prous et al (2017) reported bat necrophagy by the large South American amblypygid Heterophrynus longicornis Butler. Now, it is out of any doubt that necrophagy might be a frequent behavior in natural populations of some whip spiders.…”
Section: Preysmentioning
confidence: 73%
“…To date, there are approximately 200 extant named species, which are included in 17 genera and 4 families (Maquart & Réveillion, 2016). Nevertheless, data on its natural enemies and preys is poorly documented (Weygoldt, 2000, Armas et al, 2013, Gonçalves-Souza et al, 2014Torres-Contreras et al, 2015;Chapin & Hebets, 2016;Prous et al, 2017). Most of its known predators are scorpions and other whip spiders (intraguild competition and cannibalism), whereas the only true spider (Araneae) recorded as its predator is an undetermined Lycosidae (Chapin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whip spiders are mostly predators, also cannibalising freshly moulted individuals of the same species (Torres-Contreras et al 2015;Chapin and Reed-Guy 2017;Torres et al 2019). Yet, there are also reported cases of scavenging (García Rivera et al 2009;Prous et al 2017;Torres et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Predators of Pallas's mastiff bat include owls, falcons and the great kiskadee (Loureiro and Lim 2019). However, few large arthropods are also occasional bat predators (Molinari et al 2005;Altringham 2011;Nyffeler and Knörnschild 2013) or take advantage of carcasses (Prous et al 2017). The centipede Scolopendra gigantean was observed killing and eating individuals of three species of bats: Mormoops megalophylla, Pteronotus davyi (Mormoopidae) and Leptonycteris curasoae (Phyllostomidae) in a cave in Venezuela (Molinari et al 2005).…”
mentioning
confidence: 99%